Stimuli-Responsive Polymers Providing New Opportunities for Various Applications - KOÇAK, Gökhan; TUNCER, Cansel; BÜTÜN, Vural (Hacettepe Journal of Biology and Chemistry, 2020)
Stimuli-responsive polymers significantly change their physical or chemical properties when there is a small change in the conditions of their environments. Depending on the changes on conditions, they can self-assemble to form various nanosized structures having important usages in different fields. In this review, we report an analysis of some of the recent literatures on the basic subjects such as the architectures of different environmentally sensitive polymers, their classifications according to susceptibility and applications in various areas. During the last two decades, there have been great reports in the strategies for the preparation of novel stimuli-responsive polymers and/or polymeric materials which are suitable for various applications including materials science, nanotechnology, biotechnology, colloid and surface science, etc. In order to make this very broad polymer type more understandable to readers, basic concepts/topics are generally schematized. Furthermore, the strategies that can be followed in the production of these materials are tried to be given at a sufficient level.